SMARCA4 inactivating mutations cause concomitant Coffin–Siris syndrome, microphthalmia and small‐cell carcinoma of the ovary hypercalcaemic type. Issue 1 (25th July 2017) - Errichiello, Edoardo; Mustafa, Noor; Vetro, Annalisa; Notarangelo, Lucia Dora; de Jonge, Hugo; Rinaldi, Berardo; Vergani, Debora; Giglio, Sabrina Rita; Morbini, Patrizia; Zuffardi, Orsetta
Abstract: SMARCA4 chromatin remodelling factor is mutated in 11% of Coffin–Siris syndrome (CSS) patients and in almost all small‐cell carcinoma of the ovary hypercalcaemic type (SCCOHT) tumours. Missense mutations with gain‐of‐function or dominant‐negative effects are associated with CSS, whereas inactivating mutations, leading to loss of SMARCA4 expression, have been exclusively found in SCCOHT. We applied whole‐exome sequencing to study a 15‐year‐old patient with mild CSS who concomitantly developed SCCOHT at age 13 years. Interestingly, our patient also showed congenital microphthalmia, which has never previously been reported in CSS patients. We detected a de novo germline heterozygous nonsense mutation in exon 19 of SMARCA4 (c.2935C > T;p.Arg979*), and a somatic frameshift mutation in exon 6 (c.1236_1236delC;p.Gln413Argfs*88), causing complete loss of SMARCA4 immunostaining in the tumour. The immunohistochemical findings are supported by the observation that the c.2935C > T mutant transcript was detected by reverse transcription polymerase chain reaction at a much lower level than the wild‐type allele in whole blood and the lymphoblastoid cell line of the proband, confirming nonsense‐mediated mRNA decay. Accordingly, immunoblotting demonstrated that there was approximately half the amount of SMARCA4 protein in the proband's cells as in controls. This study suggests that SMARCA4 constitutional mutations associated with CSS are not necessarily non‐truncating, and that haploinsufficiency may explain milder CSS phenotypes, as previously reported for haploinsufficient ARID1B . In addition, our case supports the dual role of chromatin remodellers in developmental disorders and cancer, as well as the involvement of SMARCA4 in microphthalmia, confirming previous findings in mouse models and the DECIPHER database. Finally, we speculate that mild CSS might be under‐recognized in a proportion of SCCOHT patients harbouring SMARCA4 mutations. © 2017 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.